Engineering monolayer poration for rapid exfoliation of microbial membranes. Issue 2 (30th September 2016) - Pyne, Alice; Pfeil, Marc-Philipp; Bennett, Isabel; Ravi, Jascindra; Iavicoli, Patrizia; Lamarre, Baptiste; Roethke, Anita; Ray, Santanu; Jiang, Haibo; Bella, Angelo; Reisinger, Bernd; Yin, Daniel; et al.
Abstract : A novel mechanism of monolayer poration leading to the rapid exfoliation and lysis of microbial membranes is reported. Abstract : The spread of bacterial resistance to traditional antibiotics continues to stimulate the search for alternative antimicrobial strategies. All forms of life, from bacteria to humans, are postulated to rely on a fundamental host defense mechanism, which exploits the formation of open pores in microbial phospholipid bilayers. Here we predict that transmembrane poration is not necessary for antimicrobial activity and reveal a distinct poration mechanism that targets the outer leaflet of phospholipid bilayers. Using a combination of molecular-scale and real-time imaging, spectroscopy and spectrometry approaches, we introduce a structural motif with a universal insertion mode in reconstituted membranes and live bacteria. We demonstrate that this motif rapidly assembles into monolayer pits that coalesce during progressive membrane exfoliation, leading to bacterial cell death within minutes. The findings offer a new physical basis for designing effective antibiotics.